1989
DOI: 10.1097/00006842-198905000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological responses in women reporting severe premenstrual symptoms.

Abstract: Sixteen women attending a Premenstrual Tension Clinic and eight control women were tested experimentally in the premenstrual and postmenstrual phases with assessments of heart rate, skin conductance level, and neck electromyogram during rest, relaxation, an emotionally upsetting film, and performance of mental arithmetic and video game tasks. All participants completed daily symptom assessments for two menstrual cycles prior to the study. The clinic attenders were divided into eight (Clinic+) who showed marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Symptoms need to be rated daily over at least two months to confirm the diagnosis (American Psychiatric Association, 1994). Some studies show higher heart rate, greater skin conductance, or greater norepinephrine levels throughout the menstrual cycle (Palmero and Choliz, 1991; Asso and Magos, 1992; Girdler et al, 1998) or just in the late-luteal phase in women with severe PMS (Woods et al, 1994) and others show no differences in these measures compared to controls (Van den Akker and Steptoe, 1987, 1989; Girdler et al, 1993). Studies of HRV in PMS have also produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms need to be rated daily over at least two months to confirm the diagnosis (American Psychiatric Association, 1994). Some studies show higher heart rate, greater skin conductance, or greater norepinephrine levels throughout the menstrual cycle (Palmero and Choliz, 1991; Asso and Magos, 1992; Girdler et al, 1998) or just in the late-luteal phase in women with severe PMS (Woods et al, 1994) and others show no differences in these measures compared to controls (Van den Akker and Steptoe, 1987, 1989; Girdler et al, 1993). Studies of HRV in PMS have also produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Girdler et al (3) reported that women with PMDD had greater norepinephrine levels than control women both while quietly resting, and when under experimental stress conditions, regardless of menstrual phase, suggesting greater sympathetic nervous system (SNS) activity in the PMDD women. One study (4) reported that women with PMS have a higher resting heart rate than controls in the late-luteal phase, consistent with altered autonomic nervous system function, but others have failed to replicate this effect (5,6). Measures of skin conductance, used as an index of sympathetic tone, have also produced conflicting results, with some studies reporting greater skin conductance in women with PMS (7), others reporting no difference between women with PMS and controls (8), and yet others reporting higher levels of skin conductance pre-menses than post-menses in women with PMS, an effect opposite to that seen in controls (9).…”
Section: Introductionmentioning
confidence: 99%
“…The most common emotional problems are anxiety, hostility and depression. Physical symptoms such as constipation, diarrhea, sweating disorders, palpitation, dizziness and vomiting suggest autonomic nervous system (ANS) imbalance [2, 5, 10, 12,14,25,28].…”
Section: Introductionmentioning
confidence: 99%